Bacterial cellulose film coating as drug delivery system: physicochemical, thermal and drug release properties - Mohd Cairul Iqbal Mohd Amin,; Abadi Gumah Abadi,; Naveed Ahmad,; Haliza Katas,; Jamia Azdina Jamal, (Universiti Kebangsaan Malaysia, 2012)
There has been an increasing interest in the use of natural materials as drug delivery vehicles due to their biodegradability, biocompatibility and ready availability. These properties make bacterial cellulose (BC), from nata de coco, a promising biopolymer for drug delivery applications. The aim of this study was to investigate the film-coating and drug release properties of this biopolymer. Physicochemical, morphological and thermal properties of BC films were studied. Model tablets were film coated with BC, using a spray coating technique, and in vitro drug release studies of these tablets were investigated. It was found that BC exhibited excellent ability to form soft, flexible and foldable films without the addition of any plasticizer. They were comparable to AquacoatECD (with plasticizer) in tensile strength, percentage elongation and elasticity modulus. Differential scanning calorimetry (DSC) BC showed a high Tg value indicating thermally stability of films. These results suggest that BC can be used as novel aqueous film-coating agent with lower cost and better film forming properties than existing film-coating agents.